Condition optimization and efficacy for swill fermentation by Aspergillus niger - YE Ming; LIU Dong; TAN Wei; HU Shi-ming; LIU Guo-qing (浙江大学学报. 农业与生命科学版)
The culture conditions for the swill fermented by Aspergillus niger ym21 were optimized using single factor experiment and quadratic regression orthogonal rotation combination design. Single factor experiment revealed that the suitable carbon and nitrogen source were sucrose and NH4NO3, and the appropriate content of swill was 66%, and the amount of inoculum was 3% (1.4×108 spores·mL-1), and the temperature was 30 ℃. Then quadratic regression orthogonal rotation combination design was used for further optimization. It was found that the appropriate amount of sucrose and NH4NO3 was 14 and 12.67 g·L-1, respectively, and the optimal pH was 6.24. In these conditions, the average of mycelium was 20.44 g·L-1, which was slightly higher than predicted value, when A. niger ym21 was cultivated for 60 h. Protein content of the mycelium was 56.8%, and seven kinds of essential amino acids were contained. After the fermentation, most of organic substances in the swill were consumed, and the removal rates of COD and BOD5 were 86% and 90%, respectively. It not only reduced pollution caused by emission of swill, but also got relatively pure protein which could be used for feed, food additives, and so on.